Factors associated with mortality in patients hospitalized by COVID-19: a cohort study - Sánchez-Pardo, Santiago (2021)
Introduction: The area of ​​this research includes the pandemic infection called COVID 19, according to studies from several countries the factors associated with severe presentation include age over 65 years and comorbidities such as cancer, asthma, hypertension and heart disease. Objective: to describe risk factors associated with mortality in a cohort of Colombian patients hospitalized for COVID 19. Materials and Methods: Retrospective, observational, analytical study of patients hospitalized for COVID 19 who required the use of supplemental oxygen and who presented high inflammatory markers or poor prognosis, in the Hospitalization and Intensive Care Unit services in a third level center in Bogotá (Colombia) during the period from March to August 2020. Results: 214 patients were included. The age presented a mean of 58.2 years standard deviation 15.29. 60.2% were men and 39.7% women. 53.2% had personal antecedents such as: Hypertension 37.8%, Diabetes mellitus 21%, Chronic obstructive pulmonary disease 11.6%, HIV infection 6%. The risk factors found to be related to mortality were: chronic kidney disease (OR 6.68 p = 0.002 CI 2.0-22.2), Diabetes Mellitus (OR 4.6 p = 0.000 CI 2.2 - 9.6), Chronic obstructive pulmonary disease (OR 4.0 p = 0.002 CI 1.6-9.6) and male gender (OR 2.9 p = 0.008 CI 1.2 - 6.4). Conclusions: In Colombia, according to the present study, as in other countries, infection by COVID 19 has a high mortality rate at an older age and in patients with cardiovascular comorbidities (chronic kidney disease and diabetes).